Take your Positions and Shine: Effects of Positioning Aggregation‐Induced Emission Luminophores within Sequence‐Defined Macromolecules. Issue 39 (28th May 2021) - Pasch, Peter; Killa, Matthias; Junghans, Hauke Lukas; Schmidt, Melanie; Schmidt, Stephan; Voskuhl, Jens; Hartmann, Laura
Abstract: A luminophore with aggregation‐induced emission (AIE) is employed for the conjugation onto supramolecular ligands to allow for detection of ligand binding. Supramolecular ligands are based on the combination of sequence‐defined oligo(amidoamine) scaffolds and guanidiniocarbonyl‐pyrrole (GCP) as binding motif. We hypothesize that AIE properties are strongly affected by positioning of the luminophore within the ligand scaffold. Therefore, we systematically investigate the effects placing the AIE luminophore at different positions within the overall construct, for example, in the main or side chain of the olig(amidoamine). Indeed, we can show that the position within the ligand structure strongly affects AIE, both for the ligand itself as well as when applying the ligand for the detection of different biological and synthetic polyanions. Abstract : Sequence‐defined oligo(amidoamines) are employed to develop supramolecular ligands with AIE properties for detection of binding. Special focus is devoted to varying the position of the AIE luminophore within the scaffold and in relation to the supramolecular binding motif. A strong influence of the position on the resulting AIE properties is shown and evaluated for the ligand binding to various natural and synthetic polyanions.